2010
DOI: 10.1007/s10964-010-9619-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Early Maturation, Perceived Popularity, and Rumors in the Emergence of Internalizing Symptoms Among Adolescent Girls

Abstract: Despite the widely reported link between early pubertal timing and internalizing symptoms among girls, less is known about the peer reputation of earlier maturing girls. The current study assesses whether early maturation is associated with perceived popularity and/or rumors, and whether these reputational factors help account for earlier maturing girls’ vulnerability to emotional distress. Drawing on three waves of data collected from an ethnically diverse sample of middle school girls (n = 912), hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 64 publications
1
44
0
Order By: Relevance
“…In one study, exposure to peer stress partially mediated the contribution of both more advanced pubertal status and early maturation to subsequent depression in girls but not in boys (Conley et al, 2012 ). In another study, being the victim of rumor spreading among peers partially mediated the contribution of early maturation to depressive symptoms in girls (Reynolds & Juvonen, 2011 ). Exposure to stress within other-sex relationships also partially mediates the early menarchedepression association in girls (Llewellyn et al, 2012 ).…”
Section: Interpersonal Risk Pathwaysmentioning
confidence: 96%
See 2 more Smart Citations
“…In one study, exposure to peer stress partially mediated the contribution of both more advanced pubertal status and early maturation to subsequent depression in girls but not in boys (Conley et al, 2012 ). In another study, being the victim of rumor spreading among peers partially mediated the contribution of early maturation to depressive symptoms in girls (Reynolds & Juvonen, 2011 ). Exposure to stress within other-sex relationships also partially mediates the early menarchedepression association in girls (Llewellyn et al, 2012 ).…”
Section: Interpersonal Risk Pathwaysmentioning
confidence: 96%
“…In girls, maturation has some perceived social advantages, as refl ected in self-perceptions of popularity within opposite-sex relationships (Simmons, Blyth, & McKinney, 1983 ) as well as more self-rated peer support, liking, and attractiveness [for breast development, Brooks-Gunn and Warren ( 1988 ) and Tobin-Richards et al ( 1983 )] and higher levels of peer-and teacher-rated popularity (Reynolds & Juvonen, 2011 ). At the same time, these social benefi ts are intertwined with costs, such as being exposed to teasing, rumors, sexual harassment, and relational victimization from same-and other-sex peers (Brooks-Gunn, 1984 ;Craig, Pepler, Connolly, & Henderson, 2001 ;McMaster, Connolly, Pepler, & Craig, 2002 ;Reynolds & Juvonen, 2011 ), more physical (violent) victimization (Haynie & Piquero, 2006 ), and more general peer stress [e.g., poor friendship quality, peer isolation, or confl ict (Conley et al, 2012 )].…”
Section: Social Effects Of Pubertymentioning
confidence: 99%
See 1 more Smart Citation
“…Ridicule and harassment accompany off-time maturation, which give rise to exclusion and loneliness. 13,14 Many early maturing girls seek the company of older peers, so as not to stand out physically. 15 Affiliation with older peers creates vulnerability, because influence is not equally distributed between friends; younger partners tend to adopt the drinking habits of older partners.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Their results suggested that improving classroom quality may not be sufficient to improve student engagement and that additional strategies may be needed to increase the achievement for students with previous achievement difficulties. Raynolds and Juvonen (2011) assessed whether early maturation is linked with perceived popularity and/or rumors, and whether these reputational factors help account for earlier maturing girls' vulnerability to emotional distress. Drawing on three waves of data collected from an ethnically diverse sample of middle school girls (n = 912), they found, for example, that more advanced development at the start of middle school predicted peer-and teacher-reported popularity as well as increased risk of being targeted for rumors; and they also found, in turn, that rumors acted as a partial mechanism through which early maturation was associated with subsequent internalizing symptoms.…”
mentioning
confidence: 99%